Belize boosts its beans - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In 2000, Belize s bean exports reached t 2.6 million, mainly to CARICOM countries where beans are a staple food. With Brazilian support, the government has approved a US$10.5 million dollar project to develop the soybean industry, including...